Strategi Mengatasi Kemiskinan Nelayan Eretan Wetan, Indramayu - Iryana, Wahyu (Historia Madania: Jurnal Ilmu Sejarah, 2019)
Indonesia as a maritime country is rich in marine resources. However, most of the people living in coastal or coastal areas, such as the Eretan Wetan community, Indramayu with basic livelihoods of fishermen, especially traditional fishermen and fishermen, are still poor. This can be seen physically from the circumstances of residence or settlement, which looks dense and seemingly slums. The condition of this poor fisherman society is due to several things, including natural poverty, artificial, internal and external. Poverty cannot only be seen from an economic point of view, but it is related to various aspects, one of which is socio-cultural. To overcome the problem of poverty of fishermen, especially in the area of Ereten Wetan, Indramayu, it needs to be integrated in handling the problems. The responsibility of poverty alleviation fishermen not only relies on the government, but all parties involved, including Eretan Wetan own community. Eretan Wetan's poverty alleviation programs need a special strategy that is able to answer the actual conditions, so as to improve the expected well being.